Roberto Caracciolo De laudibus sanctorum kötete egy magyar prédikátor kezében - Tóthné Radó, Cecilia (Studia Litteraria, 2013)
The name and the works of Roberto Caracciolo have been well known for some time to those involved in the study of medieval Hungarian literature. He is recognised as one of the major sources for the Codex Érdy. In the past few months, we have discovered and examined a copy of Roberto Caracciolo’s De laudibus sanctorum, which supports the argument that this collection was not only a significant work of reference in Western Europe, but it proved useful for preachers in Hungary as well. The 1489 edition of De laudibus sanctorum published in Venice by Georgius Arriuabenus features an entry that lists the various religious festivals where the owner of the volume had preached, the topics of his sermons and the sources of his inspiration. There is an explicit reference to the time and place of the entry: 1495–1496, Pécs. In my study I present and discuss this unique document which justifies and supplements what we already know in the field of ars compilandi. The short drafts for sermons reveal which reference books were used by the preacher. The divisions point out the most important themes of the sermons, which can be compared with the content of the original versions. Furthermore, we can identify the method with which the subject matter was arranged and organised into a complete sermon.